From the Enigma of Identity to “Becoming a Subject”: The Transitional Double - Jung, Johann (Journal of the American Psychoanalytic Association, 2023)
In the field of psychopathology, “narcissistic and identity-related suffering” refers to a type of suffering characterized by a lack of being that centrally affects narcissism and identity continuity/discontinuity. Present in many clinical and psychopathological pictures, these problems in turn invite us to undertake a rereading of the modalities of structuration of subjectivity in the course of development. Elements for a model of identity construction are proposed based on the paradigm of the double. Approached from the angle of paradox, identity is thought of as a process in the service of “becoming a subject” based, essentially, on the role of the object and its reflexive function. Drawing on the concept of “transitional double,” this perspective allows the foundations of subjective identity and their stages of construction to be described; these foundations underlie the creation of an internal psychic mirror, the locus of one’s relationship to self. These considerations give us a better understanding of the logics of narcissistic and identity-related pathologies, which are characterized in particular by a failure of reflexive capacities, revealing the uncertainties of the dual relational dynamic in the course of early development.